The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pntd.0005384
|View full text |Cite
|
Sign up to set email alerts
|

Human cystic echinococcosis in Morocco: Ultrasound screening in the Mid Atlas through an Italian-Moroccan partnership

Abstract: BackgroundCystic echinococcosis (CE) is a neglected parasitic zoonosis with considerable socioeconomic impact on affected pastoral communities. CE is endemic throughout the Mediterranean, including Morocco, where the Mid Atlas is the most prevalent area for both human and animal infection. The highest hospital annual incidence of human CE is recorded in the provinces of Ifrane and El Hajeb. However, hospital-based statistics likely underestimate the real prevalence of infection, as a proportion of cases never … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 34 publications
7
52
2
1
Order By: Relevance
“…Our results are overall in line with those of the systematic review of Possenti and colleagues [14], and with the recent work carried out in Peru and Morocco [15, 16], individuating environmental contamination and likely “hand-to-mouth” transmission as the main factor responsible for CE transmission, while food/water source attribution likely not of primary importance.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results are overall in line with those of the systematic review of Possenti and colleagues [14], and with the recent work carried out in Peru and Morocco [15, 16], individuating environmental contamination and likely “hand-to-mouth” transmission as the main factor responsible for CE transmission, while food/water source attribution likely not of primary importance.…”
Section: Discussionsupporting
confidence: 92%
“…Owned dog-related factors (owing dogs and length of dog ownership, reason for keeping dogs, allowing dogs to roam or enter the house, antiparasitic treatment of dogs) were not found associated with odds of human infection. This may result from the dog husbandry habits in the investigated areas, which may allow environmental contamination with parasite eggs even outside the premises of the interviewed person; also a variable meaning of “owing” a dog in different areas, as also noted in previous studies, may have influenced this result [15]. Food/drinking water-related factors such as consumption of unwashed vegetables and of potentially unsafe water were also not associated with increased odds of human infection.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…9 Additional fieldwork confirmed these observations, and results of two studies focusing on the long-term follow-up of spontaneously inactivated cysts on a clinical rather than epidemiological basis, provided support to this line of conduct. [6][7][8][13][14][15][16] Hosch and others analyzed cyst material using light microscopy and ex-vivo magnetic resonance (MR) spectroscopy, and found that in CE4 and CE5 cysts no viable protoscoleces were seen on microscopy and a nonviable metabolic profile was seen on MR spectroscopy. 17 Although limited by the small sample size and the lack of information on the spontaneous or induced inactivation of CE4-CE5 cysts, and considering that light microcopy focusing on protoscolices could not provide accurate data on the viability of the germinal layer, this seminal work provides further support to field and clinical observations.…”
Section: Discussionmentioning
confidence: 99%